Analysis of inflation determinants in developing oil-export based economies - ALjebrin, Mohammad, author; Fan, Liang-Shing, advisor; Bernasek, Alexandra, committee member; Pritchett, James, committee member; Kling, Robert, committee member (Colorado State University. Libraries, 2006)
The purpose of this study is to investigate the main determinants of inflation in the developing oil-export based economies and to see if the main determinants of inflation are similar to other developing and developed economies. This study attempted to include all six Gulf Cooperation Council countries in the study. Due to the lack of data for some of these countries, the study was limited to three of them: Saudi Arabia, Kuwait and Bahrain. We made a distinction between developed and developing economies in this study. The incentive for this distinction is that the determinants of inflation are often different in these two groups. Moreover, among the developing economies, there are the developing oil-export based economies, which may have special economic structures making them unique and diverse from other economies both developed and developing, in that they have a different economic point of view, especially relating to the determinants of inflation. The tests performed in this study were carried out in three steps. The first was the test for stationarity, the second was the cointegration test, and the third was the error correction model (ECM). The outcomes of the first testing model do not offer enough evidence for the determinants of inflation in the developing oil-export based economies. Taking into consideration the characteristics of the developing oil-export based economies; a new testing model was constructed to investigate the determinants of inflation in these economies. The results of the second model provide strong evidence concerning the determinants of inflation in developing oil-export based economies. Based on these results, the main determinants of inflation in developing oil-export based economies in the long run are growth of money, growth of non-oil GDP and growth of oil prices. Moreover, in the short run, the main determinants of inflation are money growth and nonoil GDP growth.
Keywords: models; studies